Formation Of Independent Reading Skills in Primary School Students (Texas Journal of Multidisciplinary Studies, 2021)
It is used to evaluate educational standards and norms and traditionally educational outcomes. The closer the student's results are to the standard; the higher his / her learning activity is assessed. The volume of knowledge that is truly possessed and created by the learner is not fully controlled, as personal knowledge or other results that are outside the standard scope of the learner are excluded from the traditional school point of view